The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3928/01484834-20191021-04
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of a Diversity, Equity, and Inclusion Institute for Nursing Faculty

Abstract: Background: Student populations in the United States are increasingly diverse, prompting the need to make learning environments in schools of nursing more inclusive. Training for faculty is needed to support this work; however, evidence regarding best practices to make classrooms more inclusive is lacking. Method: A 3-day Diversity, Equity, and Inclusion (DEI) Institute was developed and conducted to create inclusive learning environments; facilitate cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Beard (2016), O’Connor et al. (2019), and Tengelin and Dahlborg‐Lyckhage (2017) report on the marginally positive impacts of three different professional development events. Beard’s (2016) study analysed the 'multicultural attitudes, awareness, and practices of nurse educators' (p. 439) following a one‐time training session in order to eventually diversify the nursing workforce.…”
Section: Nurse Educatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Beard (2016), O’Connor et al. (2019), and Tengelin and Dahlborg‐Lyckhage (2017) report on the marginally positive impacts of three different professional development events. Beard’s (2016) study analysed the 'multicultural attitudes, awareness, and practices of nurse educators' (p. 439) following a one‐time training session in order to eventually diversify the nursing workforce.…”
Section: Nurse Educatorsmentioning
confidence: 99%
“…O’Connor et al. (2019) report on short‐term outcomes following a 3‐day 'diversity, equity, and inclusion' (p. 633) event aimed to improve classroom inclusivity for an 'increasingly diverse' (p. 633) student population. O’Connor et al.…”
Section: Nurse Educatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Racial justice and improving health equity take on a significant role in the work of racial minority nurses (Beard & Julion, 2016). Representation of racial minority populations in nursing remains disproportionate when compared to the representation of white populations in nursing O’Connor and colleagues (2019) reported that 85% of nursing faculty nationally are white, and the landscape in which nurses operate requires them to have constructive and bold conversations and self‐reflection on racism given that nursing academia strives to not only embody an inclusive educational space but to prepare professional nurses who can deliver equitable care for a diverse population. Given the nature of white supremacy in the United States, historical, personal, social, political, and institutional norms support inequities through structural racism, to perpetuate health disparity and foster social injustice (Hardeman, Medina, & Kozhimannil, 2016…”
Section: Figmentioning
confidence: 99%